PEREMPUAN DAN PEREDARAN GELAP NARKOBA (Studi terhadap Napi di Lembaga Pemasyarakatan Perempuan Klas III Sigli Kabupaten Pidie) - Ulul Azmi; Rasyidah Rasyidah; Nurul Husna; Mahlil Mahlil (Pusat Studi Wanita UIN Ar-Raniry, 2020)
This study focuses on the causes of women's involvement in illegal drug trafficking and the forms of involvement carried out by women who are in the Class III Sigli Women's Correctional prison, Pidie Regency. The method used in this research is descriptive-qualitative method, and data collecting technique are observation, interviews and documentation. The results of this study indicate that the form of women's involvement in illegal drug trafficking, especially for women who are in the Sigli Class III Women's Correctional Prison, Pidie, namely as dealer bosses, couriers, ordinary sellers and as a place to store goods. Their involvement on average is due to economic factors which are driven by the acceleration of the process with easy access obtained from friends, husbands, or neighbors.